Assessment of Ghanaian students’ knowledge of climate change and their willingness to mitigate this phenomenon through pro-environmental practices - Adusei, Kofi (My University, 2023)
A set of questionnaires was used to ascertain the level of knowledge Ghanaian students had regarding climate change and whether the school had an impact on this level of knowledge. The items also measured students’ readiness to embrace environmentally friendly practices and their sources of knowledge about climate change. The participants of the study included students from Ghana who were in junior high, senior high, and tertiary education (N = 198). The results showed that students in Ghana had an average understanding of climate change and that their knowledge of the subject was influenced by their level of education. The results also demonstrated that the students were eager to learn more about climate change, recycling, and planting more trees. The school was the main place where students gained knowledge about climate change, followed by social media. Lastly, the study showed a weak-to-moderate relationship between students' knowledge and their willingness to engage in pro-environmental practices, with a general trend to lower correlations with increased in education level.
Keywords: Climate Change, willingness to mitigate, school, pro-environmental practices, Knowledge, Ghana, students